2020
DOI: 10.1016/j.virusres.2020.198148
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D with the modulation of the disease severity in COVID-19

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 44 publications
5
69
0
3
Order By: Relevance
“…The remaining 380 records were filtered according to the titles and abstracts; 348 were excluded due to unrelated topics. We reviewed the full text of the remaining 32 studies and identified ten that met the inclusion criteria of the meta-analysis ( Baktash et al, 2020 , Chodick et al, 2020 , Avolio et al, 2020 , Hastie et al, 2020b ; Im et al, 2020; Mardani et al, 2020 , Meltzer et al, 2020 ; Merzon et al, 2020; Raisi-Estabragh et al, 2020 , Ye et al, 2020 ).
Figure 1 Flow diagram of the literature search process.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 380 records were filtered according to the titles and abstracts; 348 were excluded due to unrelated topics. We reviewed the full text of the remaining 32 studies and identified ten that met the inclusion criteria of the meta-analysis ( Baktash et al, 2020 , Chodick et al, 2020 , Avolio et al, 2020 , Hastie et al, 2020b ; Im et al, 2020; Mardani et al, 2020 , Meltzer et al, 2020 ; Merzon et al, 2020; Raisi-Estabragh et al, 2020 , Ye et al, 2020 ).
Figure 1 Flow diagram of the literature search process.
…”
Section: Resultsmentioning
confidence: 99%
“…Most participants were at least 50 years old. Most studies were conducted in Asia (n = 5), followed by Europe (n = 4)( Baktash et al, 2020 , Avolio et al, 2020 , Hastie et al, 2020a , Raisi-Estabragh et al, 2020 ),( Chodick et al, 2020 ; Im et al, 2020; Mardani et al, 2020 ; Merzon et al, 2020; Ye et al, 2020 ), and the United States (n = 1) ( Meltzer et al 2020 ). Table 1 lists the main descriptive statistics for all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…An inverse association between mean levels of vitamin D and the number of COVID-19 cases/1 M was recently reported in a cross-sectional European study whereas a UK study did not find an association between the vitamin's status and COVID-19 risk [62]. Moreover, low levels of vitamin D were found in COVID-19 positive patients [63] or hospitalized patients with COVID-19 [64] and have been connected to the severity of the disease [65][66][67].The hypothesis that vitamin D may explain susceptibility to COVID-19 infection in dark colored skin individuals do not seem to be valid [62]. It is noteworthy that several clinical trials are on the way regarding the role of vitamin D in prevention and treatment of COVID-19, reviewed elsewhere [48].…”
Section: Vitamin Dmentioning
confidence: 88%
“…Dairy products constitute a principal source of vitamin D, which has been proposed to play a role in the COVID-19 epidemic [65][66][67]. It is noted that milk, yogurt and fermented milk products also contain PAF inhibitors [179][180][181] with a trend for a more protective effect of goat yogurt [182].…”
Section: Milk and Yogurtmentioning
confidence: 99%
“…A number of investigations confirm that deficient/insufficient concentrations of vitamin D are associated with the hospitalisation of COVID-19 patients, and less than 16 ng/mL values of the serum vitamin D have been reported to be possibly associated even with increased risk of sepsis in critically ill patients. 53 54 …”
Section: Introductionmentioning
confidence: 99%